Personal Development of Students in Higher Education - Kholbozorova Nasiba Kholbozar kizi (Zien Journals, 2023)
The article summarizes individual approaches to the study of the problem of personal development and professional development of students in the process of orientation to the profession of pedagogy in higher education, the psychological and pedagogical conditions of effective professional formation in the process of higher education, the development of students' personality by harmonizing the internal mental development of students and the external conditions of the educational process, the transition from external to internal. , the fact that selfchange and active work on oneself is a complex process are systemic features of the formation of a positive self-concept in students, it is necessary to pay attention to the formative effect of students' education in higher education, in which not only professional knowledge is formed, but also professional skills and competencies, basic professional disciplines the learning process and the result are interpreted as issues of professional and personal self-development.
Keywords: formation; approach; student